Pengaruh kepuasan kerja dan beban kerja berlebih terhadap kinerja karyawan - Suroso, Khamim; Dewie Tri Wijayati Wardoyo (Jurnal Ilmu Manajemen, 2025)
This study investigates the factors affecting employee performance at PT. Jamkrida Jatim, a regional state-owned enterprise supporting MSMEs and cooperatives. Utilizing a descriptive quantitative approach with a sample of 42 employees and a validated questionnaire, the analysis via SPSS version 25 reveals that job satisfaction and excessive workload together account for 47.7% of the variance in employee performance. While job satisfaction positively influences performance, excessive workload does not show a significant impact. These findings highlight the importance of workload management and employee well-being, offering practical insights for company management to enhance productivity and inform data-driven HR policies aimed at improving performance and supporting sustainable development in MSMEs and cooperatives.